2019
DOI: 10.1097/bpo.0000000000000944
|View full text |Cite
|
Sign up to set email alerts
|

Clubfoot and Tethered Cord Syndrome: Results of Treatment With the Ponseti Method

Abstract: Level II-retrospective prognostic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…1). 7,[16][17][18][19][20][21][22][23][24][25] The MINORS of each article was calculated which yielded scores ranging from 11/16 to 12/16 for non-comparative studies and from 18/24 to 21/24 for comparative studies. Because of the limited amount of studies reporting results on treatment of non-idiopathic clubfeet with the Ponseti method, all studies were included regardless of the MINORS.…”
Section: Resultsmentioning
confidence: 99%
“…1). 7,[16][17][18][19][20][21][22][23][24][25] The MINORS of each article was calculated which yielded scores ranging from 11/16 to 12/16 for non-comparative studies and from 18/24 to 21/24 for comparative studies. Because of the limited amount of studies reporting results on treatment of non-idiopathic clubfeet with the Ponseti method, all studies were included regardless of the MINORS.…”
Section: Resultsmentioning
confidence: 99%
“…The conventional practice has been to perform extensive soft tissue and bony surgeries to correct the deformity, which often resulted in stiff and painful feet, high relapse rates, and unsatisfactory outcomes [6][7][8][9][10][11]. Considering the poor outcomes of radical surgery and parallel with the surge of interest in conservative methods of clubfoot treatment over the past few decades, several researchers have reported on the use of the Ponseti method for these difficult feet [12][13][14][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Both studies were of a small series of 12-16 patients with amyoplasia or distal arthrogryposis and showed a variable success rate of 70-92% at a mean short-term follow-up of 3 years [12,13]. Subsequently, a few more articles in literature [14,[16][17][18][19][20][21][22][23][24][25][26] have reported on the successful short-term outcomes of the Ponseti method in non-idiopathic clubfeet. However, some of these articles have focused on a particular aetiology (Arthrogryposis, Myelomeningocele, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…But, Jackson et al concluded that clubfoot associated with constriction band required more casts to achieve an acceptable correction and had an increased risk of deformity recurrence compared with subjects with isolated clubfoot (15).…”
Section: Discussionmentioning
confidence: 99%